Population Dynamics in the Mediterranean A Demographic Convergence? - Doignon, Yoann (SpringerBriefs in Population Studies, 2023)
This open access book makes a comparative overview of the demographic evolution of the Mediterranean populations. It addresses all the demographic issues since 1950 such as fertility, mortality, growth, demographic aging, and the age structure of the population. The book discusses the major demographic changes and its consequences for the Mediterranean region and describes the socio-economic and societal opportunities such as the silver economy, improvement in health of the population, and progress in education. By providing insights into the past demographic evolutions and analyzing the most recent indicators, this book constitutes an essential reference work for those who wish to better understand the major transformations that Mediterranean societies are undergoing.